Fixings Agent Effect to β-carotene Stabilityof Crude Extract from Dunaliella salina Microalga at Different Temperature Condition - Ardini Ria Oktora; Widodo Farid Ma’ruf; Tri Winarni Agustini (Jurnal Pengolahan Hasil Perikanan Indonesia, 2016)
AbstractDunaliella salina is a microalga rich pigment carotenoids that can be used asnatural dyes. The problemfaced for temporative β-carotene stability which is unstable and easily degraded is unstable and easilydegraded. The purpose ofthis researchwas to determine content and stability of β-carotene pigment inD.salina with fixings addition of MgCO3 and NaHCO3 with temperature treatment as factor that influenceβ-carotene pigment degradation during storage condition. The research method used β-carotene pigmentwhich was obtainedbymaceration and adding fixing agent (NaHCO3 0,5% and without fixings addition),and was heated at temperature of (50°, 70° and 90°C), be measured the content of β-carotene pigmentduring storage (observation hour 0, 24, 48, 72, 96, 120 and 144). Data analyzed by ANOVA and HonestlySignificant Different (HSD). The result showed that content of β-carotene pigment at 50°C temperatureshowed that stability and pH value performed slowest degradation after144 hours. While stability and pHvalue at 90°C temperature performed fastest degradation after 96 hours. Based on this study the addition ofNaHCO3 gave more effective in retaining β-carotene degradation compared to that of MgCO3 which showedby high stability in sample NaHCO3 0,5%, temperature 50°C in 144 hours storage length.